COUNTER NARRATIVES FROM HADITH TEXTS OF KH. SYA’RONI AHMADI’S AL-FARAID AL-SANIYYA AGAINST WAHHABISM - Friyadi, Arif (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
The discourse of Ahlus Sunnah wa al-Jama'ah Islam is a topic that will not be obsolete throughout the history of Muslims. The emergence of the Salafi Wahabi sect of Islam in various Muslim countries has caused the division of Muslims. Rahmatal lil 'alamin Islam seems to be eroded by the takfiri and bid'I movements of various figures. Some of the world's scholars through their works have made a major contribution to stem this movement. Among these works is the book al-Faraid al-Saniyah by KH. Sya'roni Ahmadi, which contains the concept of countering wahabi salafi, especially in Indonesia. This research uses a qualitative-based character study which basically relies on data from interviews, supporting literature and biographies of the figures studied. The results of this study found that the purification of religion heralded by Wahabi figures by referring to the Qur'an and hadith is actually not feasible to be applied in Indonesia. A wrong understanding in the interpretation of the Qur'an and hadith will plunge a person into national disintegration. Therefore, the ahlussunah wal jama'ah creed must be upheld so that an Indonesian Muslim becomes a moderate Muslim who accepts various ikhtilaf.[Wacana Islam Ahlus Sunnah wa al-Jama’ah merupakan topik yang tidak akan ketinggalan zaman sepanjang sejarah umat Islam. Munculnya sekte Islam Salafi Wahabi di berbagai negara Muslim telah menyebabkan perpecahan umat Islam. Rahmatal lil ‘alamin Islam seakan tergerus oleh gerakan takfiri dan bid’I dari berbagai tokoh. Beberapa cendekiawan dunia melalui karya-karyanya telah memberikan kontribusi besar untuk membendung gerakan ini. Diantara karya tersebut adalah kitab al-Faraid al-Saniyah karya KH. Sya’roni Ahmadi yang berisi tentang konsep countering wahabi salafi khususnya di Indonesia. Penelitian ini menggunakan studi karakter berbasis kualitatif yang pada dasarnya mengandalkan data dari hasil wawancara, literatur pendukung dan biografi tokoh yang diteliti. Hasil penelitian ini menemukan bahwa pemurnian agama yang digembar-gemborkan oleh tokoh-tokoh Wahabi dengan berpedoman pada al-Qur’an dan hadits sebenarnya tidak layak diterapkan di Indonesia. Pemahaman yang salah dalam menafsirkan al-Qur’an dan hadis akan menjerumuskan seseorang ke dalam disintegrasi bangsa. Oleh karena itu, akidah ahlussunnah wal jama’ah harus ditegakkan agar seorang muslim Indonesia menjadi muslim moderat yang menerima berbagai ikhtilaf.]